Cryptocurrencies: a study on the opinions of respondents of IASB comment letters - Santos, Lucas Benicio dos (2023)
Due to the growing use of crypto-assets and the lack of a standardization on the subject, in May 2019, the International Accounting Standards Board (IASB) issued the Holdings of Cryptocurrencies document indicating the understanding of cryptocurrency accounting and requesting the submission of comment letters to stakeholders. Thus, this research aims to examine the comment letters received by the IASB regarding the recognition and accounting of digital currencies. Twenty comment letters were analyzed, sent by eight different accounting sectors and the results indicate that, in general, the respondents agree with the classification of crypto assets as intangibles and inventories, and they also agree or do not opine with the non-classification as cash and financial instruments. Additionally, the majority disagrees with the IASB's decision to only issue a provisional decision and not carry out a more in-depth study regarding the classification of cryptoassets.